An unusual approach for a cervical mass: sternotomy for the treatment of a giant cervico-thoracic lipoma: Sternotomy for the treatment of a giant cervico-thoracic lipoma - Petruzzi, Gerardo; Trozzi, Lucrezia; Moretto, Silvia; De Virgilio, Armando; Melis, Enrico; Gallina, Filippo Tommaso; Pichi, Barbara; Campo, Flaminia; Facciolo, Francesco; Pellini, Raul (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Lipoma is a benign mesenchymal tumor. It is a very common tumor and in 13% of cases occurs in head and neck. Giant lipomas are extraordinary and cervical involvement with mediastinal extension is an exceedingly rare presentation. Only a few cases of thoracic extension are reported in literature.Methods: We describe the case of a 62-years-old man with a giant cervico-mediastinic lipoma which required a combined approach through cervicotomy and sternotomy to ensure surgical radicality. Differential diagnoses could be thymolipoma, liposarcoma or familiar lipomatosis.Results: The mass was removed en-bloc with thymus and locoregional lymph nodes. The patient recovered uneventfully.Conclusions: The aim of this report is to discuss potential pitfalls of differential diagnosis and implementation of the therapeutic treatment. Focus on the relevance of performing fluorescence in situ hybridization (FISH) for MDM2 amplification is reported, a necessary technique for the differential diagnosis.(www.actabiomedica.it)